Voir en Peinture - Bordaz, Jean-Pierre; Bourne, Cécile; Bulteau, Michel; Corne, Éric; Falguières, Patricia; Florizoone, Jan; Theys, Hans; Tronche, Anne; Trémeau, Tristan; Verhagen, Erik; Vo, Marie-France (Bruxelles : La Lettre volée Bruxelles, 2003)
Adach, Adam ; Arthuis, Isabelle ; Bart, Cécile ; Desgrandchamps, Marc ; Janssens, Ann Veronica ; Méléder, Alix le ; Millet, Guillaume ; Mont, Miquel ; Noiret-Thomé, Xavier ; Tursic, Ida ; Mille, Wilfried ; Swennen, Walter
Voir en Peinture, Le Plateau - Frac Île-de-France, Paris, 2003-09-18. 2003-11-24
boek